Analisis Implementasi E-Health dan Telemedicine di Indonesia: Studi Kasus Program Jaminan Kesehatan Nasional (JKN) - Fadhia Chairunnisa (Diversity: Jurnal Ilmiah Pascasarjana, 2024)
This research aims to analyze the implementation of e-health and telemedicine in the National Health Insurance (JKN) program in Indonesia. Qualitative research is a method that produces descriptive data, both in the form of speech, writing and the behavior of the people being observed. This allows researchers to understand phenomena in depth through data collection that is as complete and in-depth as possible. With this method, researchers can analyze research subjects and feel what they experience in everyday life. There are findings regarding empirical evidence, strategies for increasing access and adoption of e-health and telemedicine in Indonesia. As well as criticism and recommendations for creating effectiveness and efficiency regarding Mobile JKN in improving E-Government and innovation policies. This research aims to analyze the implementation of e-health and telemedicine in Indonesia, with a focus on case studies of the JKN program in Indonesia.